THE CONTENT, FORMATION AND DEVELOPMENT OF MILITARY PEDAGOGICAL CULTURE - Qarshiyev Azamat Rahmonivich; Xuramov Jasur Musurmon o‘g‘li; Xuramov Jasur Musurmon o‘g‘li (Journals Park Publishing, 2024)
The objectives and functions of the article in the learning process, the pedagogical culture of the military, are a complex structure and context, and its formation and improvement are a long-term, continuous, a number of tools and methods.
Keywords: Culture; enlightenment; material culture; spiritual culture; pedagogical culture; a broad worldview; zukkolik and visit; pedagogical skills; aesthetic pleasure; culture of high treatment, decency of speech, followability.